Semiarid climate and hyposaline lake on early Mars inferred from reconstructed water chemistry at Gale - Keisuke Fukushi (Nature Portfolio, 2019)
Gale Crater on Mars has been demonstrated to have once hosted water, but its chemistry is still under debate. Here the authors use mineralogical rock compositions and show the once saline character of Gale Crater—a result of warmer climate periods during the Hesperian period.